Practical lighting design with LEDs - Lenk, Ron, 1958-; Lenk, Carol; John Wiley & Sons; IEEE Xplore (Online service) (Hoboken, New Jersey : Wiley-IEEE Press, 2011)
"This book covers all of the information needed to design LEDs into end-products. It is a practical guide, primarily explaning how things are done by practicing engineers. Equations are used only for practical calculations, and are kept to the level of high-school algebra. There are numerous drawings and schematics showing how things such as measurements are actually made, and showing curcuits that actually work. There are practical notes and examples embedded in the text that give pointers and how-to guides on many of the book's topics. After reading each chapter of the book, readers will have the knowledge to implement practical designs. This book will be kept as a reference tool for years to come"--
PCB Design -- Getting the Light Out -- LEDs in Harsh Environments -- Designing With the Next Generation LED in Mind -- Lighting Control -- 10 Practical Examples -- Example: Designing an LED Flashlight -- Example: Designing a USB Light -- Example: Designing an Automobile Taillight -- Example: Designing an LED Light Bulb -- 11 Practical Measurement of LEDs and Lighting -- Measuring Light Output -- LED Measurement Standards -- Measuring LED Temperature -- Measuring Thermal Resistance -- Measuring Power, Power Factor, and Efficiency -- Accelerated Life Tests -- 12 Practical Modeling of LEDs -- Preliminaries -- Practical Overview of Spice Modeling -- What Not to Do -- What to Do -- Modeling Forward Voltage -- Reverse Breakdown -- Modeling Optical Output -- Modeling Temperature Effects -- Modeling the Thermal Environment -- A Thermal Transient -- Some Comments on Modeling -- References -- Index -- IEEE Press Series on Power Engineering.
Includes bibliographical references (p. 231) and index.
Also available in print.
Mode of access: World Wide Web
Description based on PDF viewed 12/21/2015.
Keywords: Light emitting diodes; Electric lamps -- Design and construction; Electric lighting -- Design; Engineering; Electrical engineering; Electronic books